Garbhagriha of the Mahishasuramardini Temple (Temple 9) - Temples of India Project Team (Jio Institute, 2024)
In the garbhagriha (sanctum sanctorum) of the Mahishasuramardini Temple (Temple 9), a pedestal holds a sculpture of a Goddess. The Goddess is worshipped by the locals, as indicated by the vermilion on her face and the clothes that the sculpture is wrapped in.